2015
DOI: 10.7439/ijbar.v6i3.1619
|View full text |Cite
|
Sign up to set email alerts
|

Acute oral toxicity study of polyherbal formulation AV/KPC/10

Abstract: The current study was designed to study acute oral toxicity study of polyherbal formulation AV/KPC/10 (M/S Ayurvet Limited, Baddi, India) according to OECD guidelines. For new substances it is the recommended stepwise testing approach for developing scientifically sound data on the safety of the substance. Three wistar rats (2 females and 1 male) were used for the study. AV/KPC/10 in single oral dose (2000mg/kg) supplemented to all rats. The parameters like general appearance, behavior, body weight, mortality … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
2
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 5 publications
0
2
0
2
Order By: Relevance
“…In this study, we found that the body weight of all the animals increased significantly on days 8 and 15, which is consistent with the findings of [15] , who found that all the female rats treated with the polyherbal veterinary drug for 14 days saw a slight increase in body weight. Still, they could not detect any death rates or significant toxicopathological changes [18] reported that the polyherbal formulation was non-toxic despite noticing a slight increase in the body weight of all the rats used in their study.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…In this study, we found that the body weight of all the animals increased significantly on days 8 and 15, which is consistent with the findings of [15] , who found that all the female rats treated with the polyherbal veterinary drug for 14 days saw a slight increase in body weight. Still, they could not detect any death rates or significant toxicopathological changes [18] reported that the polyherbal formulation was non-toxic despite noticing a slight increase in the body weight of all the rats used in their study.…”
Section: Discussionmentioning
confidence: 87%
“…Similar finding and noted the absence of clinical symptoms following a single oral dosage of 2 mg/kg polyherbal formulation. After a single oral dosage of 2 mg/kg Body weight of Rosmarinus officinalis, [16,18] also found no unusual symptoms or behavioral alterations. Similar study found no acute mortality at 1100 mg/kg; however, there was a rapid increase in the death rate with an additional 100 mg increment in the dose.…”
Section: Discussionmentioning
confidence: 88%
“…Parameter toksisitas ditunjukkan dengan nilai LD 50 atau Lethal dose 50 yang berarti suatu nilai yang menunjukkan besarnya dosis yang dapat menyebabkan setengah atau 50% dari hewan uji mati (Gatne, et al, 2015). Parameter LD 50 dapat diperoleh dengan menggunakan program online yaitu ProTox.…”
Section: Parameter Fisika Kimiaunclassified
“…Parameter LD 50 dapat diperoleh dengan menggunakan program online yaitu ProTox. Semakin kecil nilai LD 50 yang diperoleh maka senyawa tersebut semakin toksik (Gatne, et al, 2015). Dari hasil analisis diperoleh bahwa senyawa BFKT dan 14 turunannya memiliki nilai LD 50 yaitu 2885 dan 5 turunan lainnya memiliki nilai LD50 yaitu 2850 mg/kg serta berada di kelas 5.…”
Section: Parameter Fisika Kimiaunclassified